The ecological diversity of vegetation within urban parks in the Dabrowski Basin (southern Poland) - Banaszek, Jarosław; Leksy, Marzena; Rahmonov, Oimahmad (International Conference “Environmental Engineering”, 2017)
The aim of this work is to present the diversity of flora in terms of ecological requirements. The research was conducted in the area of two urban parks in the area of two cities in southern Poland: Bedzin and Czeladz. These parks were established in different historical periods, and were planned (and are managed) differently. The results of the investigation have shown that the occurrence of 192 vascular species has been observed in the Gora Zamkowa (Castle Hill) Park, while in the Grabek park, 334 such species are known to exist. Such disparity is the result of the occurrence of microhabitats and of the differences between the ways the two parks are managed. It is also due to these parks’ different functions. In the first case, the park area is protected by law. In the latter case, human activity has created a new ecological niche for organisms with a high degree of ecological tolerance. Based on the ecological values, the following groups of plants were distinguished: saxifrages grasslands, xerothermic grasslands, beech forests, alder forests and artificial planted trees. Analysis has shown that urban parks are potential places for growth various type of vegetation and also for increasing biodiversity, and can constitute particularly important hotspots for biodiversity in the cityscape, even if their primary role is recreational. As the study shows, the environment of a highly urbanized and industrialized region can also have a positive influence on ecological and floristic diversity.
Keywords: habitat diversity; biodiversity; vegetation type; urban ecosystems; nature protection